Cross-correlating Planck with VST ATLAS LRGs: a new test for the ISW effect in the Southern hemisphere. Issue 4 (28th February 2020) - Ansarinejad, Behzad; Mackenzie, Ruari; Shanks, Tom; Metcalfe, Nigel
ABSTRACT: The integrated Sachs–Wolfe (ISW) effect probes the late-time expansion history of the Universe, offering direct constraints on dark energy. Here, we present our measurements of the ISW signal at redshifts of $\bar{z}=0.35$, 0.55, and 0.68, using the cross-correlation of the Planck cosmic microwave background temperature map with ∼0.5 million luminous red galaxies (LRGs) selected from the VST ATLAS survey. We then combine these with previous measurements based on WMAP and similar SDSS LRG samples, providing a total sample of ∼2.1 million LRGs covering ∼12 000 deg 2 of sky. At $\bar{z}=0.35$ and $\bar{z}=0.55$, we detect the ISW signal at 1.2σ and 2.3σ (or 2.6σ combined), in agreement with the predictions of lambda cold dark matter (ΛCDM). We verify these results by repeating the measurements using the BOSS LOWZ and CMASS, spectroscopically confirmed LRG samples. We also detect the ISW effect in three magnitude limited ATLAS + SDSS galaxy samples extending to z ≈ 0.4 at ∼2σ per sample. However, we do not detect the ISW signal at $\bar{z}=0.68$ when combining the ATLAS and SDSS results. Further tests using spectroscopically confirmed eBOSS LRGs at this redshift remain inconclusive due to the current low sky coverage of the survey. If the ISW signal is shown to be redshift dependent in a manner inconsistent with the predictions of ΛCDM, it could open the door to alternative theories such as modified gravity. It is therefore important to repeat the high-redshift ISW measurement using the completed eBOSS sample, as well as deeper upcoming surveys such as DESI and LSST.